2015
DOI: 10.1097/gme.0000000000000421
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating lifestyle changes to manage menopausal symptoms in women with breast cancer

Abstract: The Pink Women's Wellness Program is effective in decreasing menopausal symptoms, thus improving HRQoL. This being a pilot study, further research is recommended to investigate the benefits of combining nonpharmacological interventions for women with breast cancer to reduce their treatment-related menopausal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 51 publications
1
34
0
1
Order By: Relevance
“…Two interventions involving telephone counseling were beneficial, with one reporting a significantly improved feeling of sexual attractiveness and the other finding a trend toward improved feeling of sexual desirability (15, 27). Another intervention, employing clinic appointments and journaling, resulted in significantly improved sexual function for participants (16). Taken together, these studies support the continued investigation of physical activity interventions to improve sexual health in ECS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two interventions involving telephone counseling were beneficial, with one reporting a significantly improved feeling of sexual attractiveness and the other finding a trend toward improved feeling of sexual desirability (15, 27). Another intervention, employing clinic appointments and journaling, resulted in significantly improved sexual function for participants (16). Taken together, these studies support the continued investigation of physical activity interventions to improve sexual health in ECS.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies investigating middle-aged and perimenopausal women without a history of cancer have indicated a correlation between exercise and sexual desire (13, 14). In breast cancer survivors, randomized controlled trials of physical activity interventions have demonstrated sexual health benefits (15, 16). Although breast and endometrial cancers are both obesity-driven diseases, the effects of interventions on breast cancer survivors cannot necessarily be generalized to ECS given the differences in anatomic site and potential variances in psychological factors.…”
Section: Introductionmentioning
confidence: 99%
“…The WWRP comprises a series of research projects that broadly aim to increase understanding of women's health and lifestyle behaviours and to develop effective empirically-based interventions targeting a reduction of tobacco smoking, hazardous alcohol use, increasing water intake, improving diets and increasing physical activity. This analysis also includes individual-level baseline data from 969 Australian women from the Healthy Aging of Women Study (HOW) [26][27][28] ; the Pink Women's Wellness Program 29 ; the Bluebox Study 30 ; and the Women's Wellness After Cancer Program (WWACP, trial ongoing). For the analysis, only women aged 40-63 years were included (this age range represents the expected age range at natural menopause ± 5 years).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The study procedures and recruitment details have been outlined extensively in previous papers [26][27][28][29][30][31][32][33] . Briefly, the HOW is a longitudinal observational study of women randomly selected from the electoral roll that commenced in 2001.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Of these, 330 were excluded; 59 included fewer than 20 women per study arm and 54 were not an RCT; 126 did not clearly state a sample size calculation; 52 did not measure vasomotor symptoms as the primary outcome; 39 were secondary analysis. Following these exclusions, 214 RCT were included…”
Section: Resultsmentioning
confidence: 99%